Non‐invasive evaluation of portal hypertension using shear‐wave elastography: analysis of two algorithms combining liver and spleen stiffness in 191 patients with cirrhosis. Issue 5 (11th January 2018) - Elkrief, L.; Ronot, M.; Andrade, F.; Dioguardi Burgio, M.; Issoufaly, T.; Zappa, M.; Roux, O.; Bissonnette, J.; Payancé, A.; Lebrec, D.; Francoz, C.; Soubrane, O.; et al.
Summary: Background: Two algorithms based on sequential measurements of liver and spleen stiffness using two‐dimensional shearwave elastography (2D‐SWE) have been recently proposed to estimate clinically significant portal hypertension (hepatic venous pressure gradient [HVPG] ≥10 mm Hg) in patients with cirrhosis, with excellent diagnostic accuracy. Aim: To validate externally these algorithms in a large cohort of patients with cirrhosis. Methods: One hundred and ninety‐one patients with stable cirrhosis (Child‐Pugh class A 39%, B 29% and C 31%) who underwent liver and spleen stiffness measurements using 2D‐SWE at the time of HVPG measurement were included. Diagnostic accuracy of the 2 algorithms was assessed by calculating sensitivity, specificity, positive and negative predictive values. Results: The first algorithm, using liver stiffness <16.0 kilopascals (kPa) and then spleen stiffness <26.6 kPa, was used to rule‐out HVPG ≥10 mm Hg. In our population, its sensitivity and negative predictive value were 95% and 63% respectively. The second algorithm, using liver stiffness >38.0 kPa, or liver stiffness ≤38.0 kPa but spleen stiffness >27.9 kPa, was used to rule‐in HVPG ≥10 mm Hg. In our population, its specificity and positive predictive value were 52% and 83% respectively. Restricting the analyses to the 74 patients without any history of decompensation of cirrhosis or to the 65 patients with highly reliable liver stiffness measurement did not improve the results. Conclusion: In our population, diagnostic accuracies of non‐invasive algorithms based on sequential measurements of liver and spleen stiffness using 2D‐SWE were acceptable, but not good enough to replace HVPG measurement or to base clinical decisions. Abstract : Linked Content This article is linked to Thiele and Krag paper. To view this article visithttps://doi.org/10.1111/apt.14536 .